The Word Connection Method in Early Literacy in Early Childhood - Pasaleron, Roni; Junaidi, Apri; Rahmalia, Denny; Nurrahmi, Asra (Journal of Islamic Early Childhood Education, 2024)
This learning activity using the word connection game method is carried out as a step to motivate children in developing their imagination in order to increase vocabulary and can practice language skills. This game encourages children to think about finding new words as directed by their teacher so that the activity is fun for early childhood. This study aims to determine how the application of the word connection method game media in developing children's cognitive abilities at PAUD Ar-Rahim in Kuranji Village, Padang City. This study uses a qualitative method. Data collection techniques use observation, interview, and documentation techniques. Data analysis used is qualitative data analysis with data reduction, data presentation, and conclusion drawing steps. The results of the study show that the word connection game has an effect on early literacy as well as on the self-confidence of early childhood. Therefore, it is recommended for schools, especially teachers, to implement the word connection game in order to achieve effective results so that children are happier when learning while playing. From the results of the study at PAUD Ar-Rahim after the application of the word connection game method was able to improve children's literacy and language skills towards their self-confidence and also improve children's cognitive abilities.